MENYELESAIKAN MASALAH INTOLERANSI: ANALISIS PERAN DAN BENTUK KOMUKASI (Studi Kontroversi Pondok Pesantren Waria Al-Fatah Yogyakarta) - Muhyidin Abdillah; Nila Izzamillati (Program Studi Ilmu Komunikasi FBIK Unissula, 2021)
Indonesia is a multicultural country that upholds the values of tolerance. But along with the development of increasingly sophisticated times the value of tolerance is increasingly lost. Tolerance that is always held in high esteem is now replaced by an attitude of intolerance that is increasingly common in this increasingly sophisticated digital era. Intolerance is a serious problem that must be faced by Indonesia. The digital age makes it easy for people to spread information. However, this increasingly sophisticated era if not utilized properly will cause problems. One of them is the problem of intolerance that occurs in the waria boarding school Al-Fatah Yogyakarta. This problem occurs because there is information from a media that is still in doubt. Transvestites who are vulnerable groups whose presence is only underestimated by both the state and society. Thus, transgenders who are only a minority group often receive discriminatory actions from intolerant mass organizations. The intolerant mass organization demands to close the pesantren which is a gathering place for transvestites to study religion. So then it is interesting to study. This study aims to determine the role and form of education in solving problems of intolerance in the waria al-Fatah Islamic boarding school in Yogyakarta. This study uses a qualitative descriptive approach with Miles and Huberman analysis techniques. While data collection through observation, interviews and documentation. The results of this study are intolerance that occurs in the Al-Fatah transgender boarding school due to misunderstandings in communication and acts of intolerant mass organizations in spreading information Communication has an important role in resolving these problems. Form of communication between groups with the aim of mediating the problem successfully carried out by the parties concerned. Communication between groups consisting of pesantren, government and the community provides solutions to the problem of intolerance.